Mini Grids in Nigeria : A Case Study of a Promising Market - Energy Sector Management Assistance Program (World Bank, Washington, DC, 2017)
The mini grid sector in Nigeria started to develop only recently. The study focuses on mini grids defined as small, privately-owned and operated systems with generation of up to 10 megawatts (MW) capacity and a network that distributes power to several customers. The report is to provide a cross-country comparison of these topics: it examines side by side how each of the countries studied have responded to a specific regulatory question, and presents a decision-tree approach to developing regulatory frameworks for mini grids. This document is structured as follows: (i) Section 1 starts with brief introduction; (ii) Section 2 has brief description of the context of the country; (iii) Section 3 sets out an overview of the power sector; (iv) Section 4 examines the main aspects of the policy setting for mini grids; (v) Section 5 surveys technologies and business models used in the mini grids sector; (vi) Section 6 explains the process to authorize mini grid operators; (vii) Section 7 assesses technical and service standards for mini grids; (viii) Section 8 explains tariff setting, financing, and subsidies; (ix) Section 9 describes handling the relationship with the main grid; and (x) Section 10 concludes with a summary of lessons learnt from the experience of the country.